Array‐CGH is an effective first‐tier diagnostic test for EFTUD2‐associated congenital mandibulofacial dysostosis with microcephaly. (20th December 2013) - Gandomi, S.K.; Parra, M.; Reeves, D.; Yap, V.; Gau, C.‐L.
<x xml:space="preserve">Abstract</x> Mandibulofacial dysostosis with microcephaly (MFDM) is a sporadic malformation syndrome with severe craniofacial abnormalities, microcephaly, developmental delay, and dysmorphic features. Most cases of clinically diagnosed MFDM remain genetically unexplained, and to the best of our knowledge a total of 35 patients, 31 different mutations, 4 deletions, and 6 reports have been published. Our proband was born at 36 weeks gestation with microcephaly, microcrania, cleft palate, severe retrognathia, oral and pharyngeal dysphagia, bilateral proximal radioulnar synostosis, 11 thoracic ribs, abnormal magnetic resonance imaging (MRI) findings including simplified gyral pattern and mild dilatation of the posterior bodies of the lateral ventricles secondary to thinning of the white matter, high‐pitched cry due to unilateral vocal cord paralysis, and dysmorphic features. Array comparative genomic hybridization (aCGH) + single nucleotide polymorphism (SNP) analysis identified a likely de novo pathogenic deletion on chromosome 17q21.31, encompassing the EFTUD2 gene. Our case represents the fifth reported proband to have MFDM caused by small deletions involving EFTUD2. All known mutations involving EFTUD2 result in genetic haploinsufficiency, consistent with our proband's case as well. Her phenotypic features both overlap and expand on the clinical features of previously reported cases, and her genetic diagnosis also supports the use of aCGH as a first‐tier testing option for this disorder.